PENGUKURAN KESENJANGAN DIGITAL MASYARAKAT DI KABUPATEN SUMBA BARAT DAYA - Gergorius Kopong Pati (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTInformation and communication technology (ICT) related with government in developing and formulating public service policy strategies has vast benefits in accessing, managing and having very accurate and fast information. Lack of information technology leads to digital divide, so measurement is necessary. Result of measurement of digital divide can be used as reference by government in distributing information and communication technology access and skill to the society by providing infrastructures, training programs for develop human resources.SIBIS (Statistical Indicators Benchmarking the Information Society) is the result of an action of the European Commission to compare various indicators to measure digital divide. The measurement uses SIBIS GPS (General Population Survey) indicator using aspects of internet usage behavior, internet usage benefit and e-government. The populations were 18 – 59 years old people in four sub-districts and 125 respondents were selected by Proportionate Stratified Random Sampling. The result of the measurement of digital divide showed there was digital divide among Northwest Sumba people, showing lack of socialization and training program, as well as inadequate human resources.Keywords: Digital divide, SIBISABSTRAKTeknologi informasi dan komunikasi(TIK) yang berkaitan dengan pemerintah dalam membangun dan menyusun strategi kebijakan pelayanan publik memiliki manfaat yang luas dalam pengaksesan, pengelolaan serta memiliki informasi yang sangat akurat dan cepat. Kurangnya teknologi informasi mengakibatkan terjadinya kesenjangan digital sehingga perlu dilakukan pengukuran. Hasil dari pengukuran kesenjangan digital tersebut dijadikan bahan acuan dalam pemerataan akses dan kemampuan teknologi informasi dan komunikasi bagi masyarakat melalui penyediaan infrastruktur, program pelatihan untuk pegembangan sumber daya manusia.SIBIS (Statistical Indicators Bechmarking the Information Society) adalah hasil kegiatan komisi eropa (European Commision) yang digunakan dalam membandingkan berbagai macam indikator yang berbeda untuk pengukuran kesenjangan digital. Pengukuran ini menggunakan indikator SIBIS GPS (General Population Survey) dengan menggunakan aspek perilaku penggunaan internet, kegunaan penggunaan internet dan e-government. Populasi dilakukan pada masyarakat diempat kecamatan yang berusia 18 – 59 tahun, dan diambil 125 responden dengan metode Proportionate Stratified Random Sampling.Kata Kunci : Kesenjangan digital, SIBIS